An Evidence-Based Systematic Review of Elderberry and Elderflower (Sambucus nigra) by the Natural Standard Research Collaboration. (1st March 2014) - Ulbricht, Catherine; Basch, Ethan; Cheung, Lisa; Goldberg, Harley; Hammerness, Paul; Isaac, Richard; Khalsa, Karta Purkh Singh; Romm, Aviva; Rychlik, Idalia; Varghese, Minney; Weissner, Wendy; Windsor, Regina C.; et al.
ABSTRACT An evidence-based systematic review of elderberry and elderflower (Sambucus nigra) by the Natural Standard Research Collaboration consolidates the safety and efficacy data available in the scientific literature using a validated, reproducible grading rationale. This article includes written and statistical analysis of clinical trials, plus a compilation of expert opinion, folkloric precedent, history, pharmacology, kinetics/dynamics, interactions, adverse effects, toxicology, and dosing.